Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Section: 246 pages : tableaux, graphiques en couleur ; 28 cm
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires